A comparison benefit reserves of an n–year term life insurance between using the vasicek model and cox-ingersoll-ross model - Kamila, Isti; Andriyati, Ani; Rohaeti, Embay (Universitas Islam Negeri Raden Intan Lampung, 2024)
The purpose of this study was to determine benefit reserves with the premium sufficiency method that would be applied to types of term insurance with non-constant interest rates by using the Vasicek and Cox-Ingersol-Ross models. The novelty of this study is in determining term insurance benefit reserves by comparing benefit reserves using the Vasicek and Cox-Ingersol-Ross interest rate models so that it can be a decision-maker for insurance companies. The stages of this research activity started by estimating the parameters for the Vasicek and Cox-Ingersoll-Ross (CIR) interest rates. The next step was to estimate the interest rate on Vasicek and CIR. Then, estimate the reserve value of term insurance benefits using the premium sufficiency method with non-constant interest rates. At the final stage, the results of the reserve value of benefits with non-constant interest rates and CIR would be interpreted and compared. The results of the research obtained by the CIR interest rate were always positive, and the difference in interest rates between each time was not too large compared to Vasicek. This was in line with the reserve results of the benefits obtained. The difference in benefit reserves between times using Vasicek was greater than that of the CIR interest rate model.